Relative efficiency of the electric power distribution sector in Peru: an application of Data Envelopment Analysis (DEA) - Bonifaz F., Jose Luis (2000)
The aim of this paper is to analyze the technical efficiency of the companies that operated on the electric power distribution sector in Peru from 1995 to 1998. For this purpose we will employ Data Envelopment Analysis (DEA), and we will point out the main advantages and limitations of this technique. This well-known non-parametric and deterministic tool is used to empirically build the production frontier in this sector. Finally, we will discuss about the topic of efficiency in the public sector comparing the average performance according with the ownership of the capital for public, privatized and private companies. From this empirical analysis we conclude that the privatization process, per se, does not suppose improvements of efficiency respect to public companies if we do not capture others characteristics of the market.